2016
DOI: 10.1016/j.phrp.2015.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Are Free Maternity Services Completely Free of Costs?

Abstract: ObjectivesThe Government of Nepal revised free maternity health services, “Aama Surakshya Karyakram”, beginning at the start of Fiscal Year 2012/13, which specifies the services to be funded, the tariffs for reimbursement, and the system for claiming and reporting on free deliveries each month. This study was designed to investigate the amount of monetary expenditure incurred by families using apparently free maternity services.MethodsBetween August 2014 and December 2014, a hospital-based cross-sectional stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 9 publications
0
30
0
Order By: Relevance
“…Ten studies were published between 2000 and 2010 25,27,28,38,39,41,48,[51][52][53] while the remaining 26 were published post-2010. 26,[29][30][31][32][33][34][35][36][37]40,[42][43][44][45][46][47]49,50,[54][55][56][57][58][59][60] Figure 2 shows the geographical distribution of LMICs having at least one published study on the cost of maternal health service utilisation. Fifteen lowincome countries have published costing studies focused on maternal health service utilisation.…”
Section: Overview Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Ten studies were published between 2000 and 2010 25,27,28,38,39,41,48,[51][52][53] while the remaining 26 were published post-2010. 26,[29][30][31][32][33][34][35][36][37]40,[42][43][44][45][46][47]49,50,[54][55][56][57][58][59][60] Figure 2 shows the geographical distribution of LMICs having at least one published study on the cost of maternal health service utilisation. Fifteen lowincome countries have published costing studies focused on maternal health service utilisation.…”
Section: Overview Of Studiesmentioning
confidence: 99%
“…Fifteen lowincome countries have published costing studies focused on maternal health service utilisation. This includes three each in Nepal 42,46,53 and Tanzania, 37,41,52 two each in Ethiopia 32,55 and Mali, 40,57 and one each in Benin, 51 Burkina Faso, 38 Madagascar, 43 Pakistan, 36 and Rwanda. 50 Twenty lowermiddle income countries have published costing studies including nine studies published on India, 25,[28][29][30]33,34,47,48,56 four studies in Nigeria, 27,45,49,59 two each in Bangladesh, 31,39 and Zambia, 58,60 and one each in Ghana, 51 Kenya, 41 Lao PDR, 44 and Morocco.…”
Section: Overview Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies in Africa and Asia have shown that OOP payments still persisted in the midst of fee exemptions policies, especially for skilled attendance at childbirth [ 11 , 20 25 ]. This phenomenon is attributed to systemic challenges [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…From each city we took 50 patients from clinics and 50 from government hospitals. If we see results on the basis of rational and irrational [21][22][23][24][25] then see that rational prescribing was 48, 41, 45 and 43 in Gujranwala, Okara and Wazirabad and in Hafiz Abad respectively and irrational prescribing was 52, 59, 55 and 57 in Gujranwala, Okara and Wazirabad and in Hafiz Abad respectively (Table 2).…”
Section: Evaluation On the Basis Of Citiesmentioning
confidence: 97%